Effect of ketone bodies on viability of human breast cancer cells (MCF-7) - YALÇIN, AHMET SUHA; YILMAZ GÖLER, AYŞE MİNE (MARMARA UNIV, FAC MEDICINE, 2018)
Objective: Cancer cells exhibit an elevated glycolytic phenotype under aerobic conditions, which is known as the Warburg effect. Recent studies have also shown that cancer cells are glucose-dependent and cannot use ketone bodies as a primary source of energy. In this study, we have investigated the effects of ketone bodies on viability of breast cancer cells considering that breast cancer cells would not use ketone bodies as a primary energy source. Materials and Methods: In this study we have used MCF-7 cells, which are breast cancer cells that cannot use ketone bodies as a primary energy source and human foreskin fibroblast cells (HFF) as controls. We measured cell viability in both cells cultured in the presence or absence of glucose as well as the ketone bodies acetoacetate and beta-hydroxybutyrate. Results: Cell viability was significantly decreased in response to ketone bodies compared with control media in MCF-7 cells whereas in control cells (HFF) cell viability was not changed. Conclusion: In light of the data obtained, we suggest that dietary manipulation with the use of ketone bodies may be a new therapeutic strategy for breast cancer.
Keywords: Acetoacetate; Beta-hydroxybutyrate; ketone bodies; MCF-7 cancer cells; MITOCHONDRIA; METABOLISM